PERBANDINGAN PENDAPATAN NELAYAN TANGKAP (PAYANG DAN BAGAN) DI NAGARI MUARA KANDIS KECAMATAN LINGO SARI BAGANTI KABUPATEN PESISIR SELATAN - doby kurniawan; Yudi Antomi (JURNAL BUANA, 2021)
This study aims to see the reach of fish catch, type of fish catch, fishermen's income, comparison of fishermen's income, and the factors that affect the income of Payang and Bagan fishermen in Nagari Muara Kandis, Linggo Sari Baganti District. The data used are primary data using a questionnaire instrument and interview respondents. This research uses descriptive quantitative analysis method using survey methods and field interviews, namely research that takes a sample from one population and uses a questionnaire as a data collection tool. In this study, the data sources used are primary data and secondary data, namely data taken and collected based on data in the field taken using a questionnaire/questionnaire distributed to the selected sample and then processed.